PRODUCTION OF RICINOLEIC ACID FROM CASTOR BEAN - Maulani, Resti
Castor oil can be extracted from castor beans (Ricinus communis). Castor plants can be grown all year round in tropical and subtropical climates. The castor plant has been produced in Indonesia, but still not enough to meet industrial needs in Indonesia, so castor oil must be imported. Castor oil is dominated by ricinoleic acid with content of 85 – 90% which can be utilized to produce derivative products with a higher selling price than crude castor oil, such as raw materials for making polymers, lubricants, and cosmetics. The conventional method, namely Colgate-Emery, the condition of hydrolysis is at a temperature of 260 oC and 50 bar pressure. But, in this research, ricinoleic acid is produced from hydrolysis with lipase as catalyst, so it requires less energy, low thermal degradation, less by-products resulting in high purity, and can produce unsaturated fatty acids without oxidation. The lipase enzymes are from castor beans which are immobilized into acetone powder to increase the effectiveness and stability of the enzyme. Longenecker and Haley (1937) report that acetone powder is less active compared to lipase powder made with pentane & ether solvents. Allegedly, the free glycerol in the castor bean, which protects the lipase from denaturative disturbance, is also extracted by acetone, which decreases the activity of acetone powder. In this research, it is concluded that addition of glycerol in the acetone as solvent affecting badly to the activity of lipase powder hydrolysis. This research also shows that hydrolysis is better in room temperature (25–37 oC) for 3 days. This condition is then applied to scales of 15, 40, and 50 grams oil. The average percentage of highest was obtained on the scale of 15 grams oil, at 82,76%.